Perubahan Struktur Produksi Pertanian dan Dampaknya terhadap Interaksi Sosial-Keagamaan Masyarakat Muslim Bilah di Dusun Tolok - Suhaimi Umar Harahap (Medan Resource Center, 2024)
This study examines the process of change in the agricultural production structure in Tolok Hamlet and its impact on social interactions and socio-religious practices within the Bilah Muslim community. The research aims to analyze how shifts in agricultural commodities occurred and how these transformations influenced patterns of social relations and religious life in a rural Muslim society. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, participant observation, and documentation. Informants consisted of local community leaders, oil palm farmers, former rice and rubber farmers, and village officials who were directly involved in or affected by changes in agricultural production. The findings reveal that the Bilah Muslim community initially relied on subsistence rice farming to meet basic needs. However, limited irrigation infrastructure, recurrent flooding, and declining productivity encouraged a transition to rubber plantations. This shift was short-lived due to high rainfall and frequent crop failures. The most significant transformation occurred with the introduction of oil palm plantations initiated by PT. Socfindo in 1978, which offered greater economic stability and has since become the dominant livelihood source in Tolok Hamlet. These changes in agricultural production structure have reshaped social interactions, particularly in consumption patterns, perceptions of land value, labor relations, and access to production capital. Furthermore, socio-religious practices have also transformed, including changes in the meaning of work in Islam, patterns of mutual cooperation (gotong royong), and practices of charity and mutual assistance. This study contributes to the discourse on social change in rural Muslim communities by highlighting the intersection between economic transformation and socio-religious dynamics within the framework of Islamic rural sociology.